Analysis of critical thinking test instruments on the Light Waves concept (CT-LiWa): Rasch model - Raldy Aditya; Endi Suhendi; Lina Aviyanti; Abu Nawas; Heni Rusnayati (Momentum: Physics Education Journal, 2025)
This research aims to develop an instrument that measures students' critical thinking skills in physics learning to test its validity and reliability using the Rasch Model. The instrument is called the Critical Thinking Test on The Light Waves Concept (CT-LiWa). The novelty of this research is to create a new instrument that is applied to the concept of light waves. The target of this instrument is high school students in one of the provinces in West Java. This research method uses the ADDIE model involving 72 high school students from West Java, Indonesia. The instrument used is a validation sheet and the CT-LiWa consists of 15 items in the form of descriptions. The trial results data were analyzed using the Rasch Model assisted by the Winstep program to obtain the quality of the instrument, namely reliability, validity, and level of difficulty. The results of the analysis show that the CT-LiWa test is not reliable but has a good validity of 27.6% in the fulfilled category with varying levels of difficulty. Therefore, the development of the CT-LiWa test can be implemented as an instruent to measure students' critical thinking skills on the concept of light waves.